2018
DOI: 10.1007/82_2018_105
|View full text |Cite
|
Sign up to set email alerts
|

Enteroaggregative Escherichia coli

Abstract: Enteroaggregative Escherichia coli (EAEC, formerly known as "EAggEC") cause acute or persistent watery diarrhoea (with or without mucus) in children, predominantly in low-income countries, and are associated with travellers' diarrhoea in children and adults in middle and high income countries. The diverse nature of EAEC is such that not all strains cause disease. Conversely, certain strains of EAEC possess additional virulence determinants associated with the ability to cause severe diarrhoea and other symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 80 publications
0
21
0
10
Order By: Relevance
“…After ETEC, EAEC is the second most common cause of tourista that causes acute and sometimes persistent diarrhea (Jenkins, 2018). The diarrhea is typically non-bloody and without inflammation or emetic symptoms.…”
Section: Physiopathology Of Decmentioning
confidence: 99%
See 1 more Smart Citation
“…After ETEC, EAEC is the second most common cause of tourista that causes acute and sometimes persistent diarrhea (Jenkins, 2018). The diarrhea is typically non-bloody and without inflammation or emetic symptoms.…”
Section: Physiopathology Of Decmentioning
confidence: 99%
“…EAEC form a loose biofilm at the mucosal surface involving pili and especially AAF (aggregative adhesion fimbriae, encoded by a large plasmid pAA) (Kaper et al, 2004;Ageorges et al, 2020). Additional virulence factors include the pAA-encoded enterotoxins EAST1 and Pet (plasmid-encoded toxin) and the chromosome-encoded ShET1 (Shigella enterotoxin 1) and Pic (protein involved in intestinal colonization) (Chaudhuri et al, 2010;Jenkins, 2018). However, the molecular basis that mediates diarrhea upon infection by EAEC remains to be elucidated.…”
Section: Physiopathology Of Decmentioning
confidence: 99%
“…The action of these inhibitory molecules, which affects phylogenetically related bacteria, can be vital for the health of the host organism. E. coli occurs not only as a commensal organism in the intestines of warm-blooded animals but also as six well-studied pathotypes causing morbidity and mortality [ 18 , 19 , 20 , 21 , 22 ]. What is more, E. coli bacteria in their primary intestinal environments are exposed to the antibiotics consumed by their host, so as a consequence, the high selection pressure results in the emergence of resistant strains [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…AggR has been described in EAEC as an important transcriptional activator of at least 44 virulence genes, such as those encoding AAFs and a dispersin (antiaggregation protein) [ 19 24 ]. Nonetheless, this pathotype is a genetically very heterogeneous bacterial group, whereas recent studies have found virulence factors statistically correlated with disease, although EAEC complete pathogenesis process remain unclear [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%